2016
DOI: 10.1590/s0100-736x2016000900020
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure and Schirmer tear test values in maned wolf (Chrysocyon brachyurus)

Abstract: RESUMO.-[Pressão intraocular e teste lacrimal de Schirmer em lobos-guará (Chrysocyon brachyurus).]O objetivo deste estudo foi estabelecer dados de referên-cia sobre a produção lacrimal (STT-1) e pressão intraocular (PIO) em lobos-guará em cativeiro. Foram utilizados 10 lobos-guará, saudáveis e adultos. Os animais foram contidos com cambão e mordaça e mantidos em decúbito lateral esquerdo. O TLS foi realizado no terço médio da pálpebra inferior, durante um minuto. A córnea foi dessensibilizada e a PIO mensurada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Radinsky [40] writes in his study that the South African Painted Dogs has the same number of chromosomes and similar neuroanatomy as the domestic dog (Canis lupus familiaris). Unfortunately there are fewer studies concerning the exact orbit and eye anatomy or studies in the fied of veterinary opthalmology in canines of the Atelocynus, Cuon, Cerdocyon [21,41,42], Chrysocyon [41,43] Dusicyon, Lycalopex, Nyctereutes, Otocyon, Speothos, Urocyon, and Vulpes genus than of the Canis genus (and the Canis lupus familairis in particular). Hence, the presented results significantly expand the existing knowledge on comparative anatomy in the orbit, eye and chosen accessory organs in wild Canidae.…”
Section: Discussionmentioning
confidence: 99%
“…Radinsky [40] writes in his study that the South African Painted Dogs has the same number of chromosomes and similar neuroanatomy as the domestic dog (Canis lupus familiaris). Unfortunately there are fewer studies concerning the exact orbit and eye anatomy or studies in the fied of veterinary opthalmology in canines of the Atelocynus, Cuon, Cerdocyon [21,41,42], Chrysocyon [41,43] Dusicyon, Lycalopex, Nyctereutes, Otocyon, Speothos, Urocyon, and Vulpes genus than of the Canis genus (and the Canis lupus familairis in particular). Hence, the presented results significantly expand the existing knowledge on comparative anatomy in the orbit, eye and chosen accessory organs in wild Canidae.…”
Section: Discussionmentioning
confidence: 99%
“…Schirmer tear test values for the ring‐tailed coati (2.50 ± 2.39 mm/min) are lower than what has been described for other carnivores, such as ferrets (5.31 ± 1.32 mm/min 8 and 7.4 ± 1.9 11 ), cats (17.00 mm/min), 18 dogs (20.20 ± 2.50 mm/min), 19 crab‐eating foxes (13.37 ± 0.94 mm/min), 20 and maned wolves (11.00 ± 5.00 mm/min) 21 . The small size of palpebral fissure length may have influenced the introduction of the STT strip on the conjunctival sac of the juveniles, leading to the low values found.…”
Section: Discussionmentioning
confidence: 96%
“…Applanation tonometry values have been established for other carnivores, such as ferrets (14.50 ± 3.27 mmHg), 8 crab‐eating foxes (10.43 ± 0.96 mmHg), 20 maned wolves (20.00 ± 6.00 mmHg), 21 and lions (23.90 ± 4.10 mmHg) 29 . Despite having the lowest STT of carnivores studied to date, the IOP values found for the ring‐tailed coati with TonoPen® XL (18.66 ± 4.16 mmHg) are higher than several other species.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the results of the STT to the mentioned reports, the tear production matches that of both studies. The reports also mention that there was no significant difference between the left and right eye or between the sexes, but Carvalho et al (2020) found weak-to-moderate negative correlation between age and STT values, whereas Honsho et al (2016) found no correlations between tear test results and age trend. This difference, though, has to be studied further, with a greater number of animals.…”
Section: Ophthalmologymentioning
confidence: 97%